2008
DOI: 10.5360/membrane.33.173
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Oxidized and Fragmented Superoxide Dismutase Recruited on Liposome Surface

Abstract: The interaction of oxidized and fragmented SOD with liposomes has been reported to induce the original SOD-like enzymatic activity (L.Q. Tuan et al., Langmuir, 24 (2008) 350-354). The effect of several kinds of liposomes on their recruited activity of oxidized and fragmented SOD was first investigated. The addition of zwitterionic liposomes with high membrane fluidity or that with positive charge was found to increase the SOD-like activity of fragmented SOD although the negatively charged liposome has no effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It has recently been reported that the activity of fragmented superoxide dismutase (SOD) with no specific conformation and no activity is enhanced under an oxidative stress condition in the presence of liposome prepared by 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) through enhancement of the interaction between the fragmented SOD and the liposome [17][18][19]. It has recently been reported that the liposome itself can affect in vitro gene expression by selecting the green fluorescent protein (GFP) as a reporter protein [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that the activity of fragmented superoxide dismutase (SOD) with no specific conformation and no activity is enhanced under an oxidative stress condition in the presence of liposome prepared by 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) through enhancement of the interaction between the fragmented SOD and the liposome [17][18][19]. It has recently been reported that the liposome itself can affect in vitro gene expression by selecting the green fluorescent protein (GFP) as a reporter protein [20].…”
Section: Introductionmentioning
confidence: 99%